MUSINT 2 Nuove esperienze di ricerca e didattica nella museologia interattiva - Jasink, Anna Margherita; Family Name Deactivated, Given Names Deactivated (Strumenti per la didattica e la ricerca, 2016)
Musint 2 is a text to be read, accompanying the new MUSINT II website, following and innovating the general features of the previous MUSINT. But, as the two on-line projects differ in both technical aspects and content while maintaining similar principles and purposes, so the new volume takes on a role that makes it a novelty more suited to the progress that characterises the archaeological disciplines under a scientific and didactic perspective. The division into three sections is still maintained. The first section contains a series of works directly related to the MUSINT II site. There is an increase in the number of presentations relating to technical and educational aspects, which are considered an innovation of the new site, compared with scientific contributions intended in a more traditional sense. The second section presents an array of significant works of virtual musealisation, specifically chosen from the most varied areas, and tries to underline their educational approach. The third section is developed in continuity with the previous edition, although it presents new features in the choice of the selected research works: in fact, it selects topics which were already proposed in their experimental phase, as well as new research that have been identified over the years through the wider knowledge on the possibilities of a digital and interactive museology.